2020
DOI: 10.3390/s20061555
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric Stationarity Omnibus Test (PSOT) for Selecting Persistent Scatterer Candidates with Quad-Polarimetric SAR Datasets

Abstract: In the traditional single polarimetric persistent scatterers interferometric (PSI) technology, the amplitude dispersion index (ADI) is usually used to select persistent scatterer candidates (PSC). Obviously, based on single polarimetric information, it is difficult to use the statistical characteristics for comprehensively describing the temporal stability of scatterers, which leads to a decrease in persistent scatterer (PS) density. Considering that the temporal polarimetric stationarity of PS, the paper is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Almost at the same time, an advanced PolPSI-COH technique [34] and the coherency matrix decomposition (CMD) method (which can be used as both PolPSI-ADI and POlPSI-COH) [36] have been proposed and evaluated on Sentinel-1 PolSAR images over San Fernando Valley and Mexico city, respectively. These studies have demonstrated the effectiveness of PolPSI with Sentinel-1 PolSAR images, and researchers have shown an increased interest in PolPSI techniques recently [39,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Almost at the same time, an advanced PolPSI-COH technique [34] and the coherency matrix decomposition (CMD) method (which can be used as both PolPSI-ADI and POlPSI-COH) [36] have been proposed and evaluated on Sentinel-1 PolSAR images over San Fernando Valley and Mexico city, respectively. These studies have demonstrated the effectiveness of PolPSI with Sentinel-1 PolSAR images, and researchers have shown an increased interest in PolPSI techniques recently [39,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…The first paper [ 1 ], “Polarimetric Stationarity Omnibus Test (PSOT) for Selecting Persistent Scatterer Candidates with Quad-Polarimetric SAR Datasets”, proposes the polarimetric stationarity omnibus test method for improving the spatial density and the phase quality of persistent scatterer (PS) points. The experimental results show that the proposed method can achieve the polarimetric optimization of the interferometric phase of the PS, suppress the sidelobe of the strong scatterer effectively, and hence better reveal the details of the ground object.…”
Section: Special Issue Contentsmentioning
confidence: 99%